Study on roll-stability model optimization for partially filled tanker trucks. (April 2019) - Yu, Di; Chu, Jiangwei
In this article, a motion model for the liquid center of gravity in a truck's partially filled tank is established to solve the roll-stability problem that can occur during vehicle maneuvers. A calculation for the overturn moment, together with a liquid-sloshing equivalent mechanical model, was coupled with the partially filled vehicle motion model using an improved optimization method based on a genetic algorithm for optimizing tank geometry. Four optimized geometries were calculated to select the best roll stability, and numerical simulation results showed that the elliptical cross-section tank, with a  = 1.6–1.7 m (long axis) and b  = 1.15–1.25 m (short axis), exhibits the best stability. These results can provide a valuable benchmark for vehicle design and roll-stability analysis.